Rate of reinfections after SARS-CoV-2 primary infection in the population of an Italian province: a cohort study. (8th September 2021) - Flacco, M E; Acuti Martellucci, C; Soldato, G; Carota, R; Fazii, P; Caponetti, A; Manzoli, L
Abstract: Background: Current data suggest that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) reinfections are rare, but no information are available on minors and after 12 months of follow-up. Methods: This retrospective cohort study included all the population of an Italian Province, diagnosed with a SARS-CoV-2 infection from March 2020 to May 2021. The primary outcome was the incidence of a reinfection, defined as a new positive polymerase chain reaction (PCR) test occurring ≥90 days after complete resolution of the first infection, and data were retrieved from the official datasets (coronavirus disease 2019 [COVID-19], demographic, hospital and co-pay exemption) of the Local Health Unit (LHU) of Pescara. Results: After an average of 201 days of follow-up (max. 414), we recorded 24 reinfections ≥90 days after the resolution of the first 7173 infections (0.33%). Four reinfections required hospitalization, one was lethal. Most of the reinfections ( n = 13) occurred 6–9 months after the resolution of the first infection; no new infection was detected 12 or more months later and among the 832 minors. Conclusions: This study confirms previous findings on a low risk of SARS-CoV-2 reinfection. If confirmed, these findings suggest that more targeted restriction policies can be applied to the subjects that recovered after a first infection.